Kontribusi Big Data Analytics dalam Proses Audit Terhadap Audit Delay dan Kualitas Audit - Dian Karunia Shalihah; Wita Ramadhanti (sekolah Tinggi Ilmu Ekonomi Dharma Putra Semarang, 2025)
The use of Big Data Analytics (BDA) in the financial audit process has altered the traditional audit method by improving audit quality and efficiency. The purpose of this study is to critically assess BDA's role in reducing audit delays and increasing audit quality. Using a literature review approach, this study intends to consolidate findings from national and international studies published between 2017 and 2024 that focus on the role of BDA in audit procedural transformation, fraud detection, and real-time decision support. The findings reveal that BDA not only allows auditors to review massive amounts of data in real time, but it also improves evidence collection and risk assessment. Audit delay has emerged as a significant variable in the relationship between BDA and audit quality, however its effectiveness varies depending on technical infrastructure and auditor expertise. Furthermore, this study identified implementation problems for BDA, such as data security threats, technology literacy gaps among auditors, and organizational readiness, all of which must be addressed in order for BDA to reach its full potential. This study adds to the theoretical and practical discussions about the strategic use of BDA to alter audit methods in the digital era.